Locoregional control using highly conformal flank target volumes and volumetric-modulated arc therapy in pediatric renal tumors: Results from the Dutch national cohort. (June 2021) - Mul, Joeri; van Grotel, Martine; Seravalli, Enrica; Bosman, Mirjam E.; van Tinteren, Harm; Roy, Prakriti; Dávila Fajardo, Raquel; Tytgat, Godelieve A.M.; Mavinkurve-Groothuis, Annelies M.C.; van de Ven, Cornelis P.; Wijnen, Marc H.W.A.; de Krijger, Ronald R.; et al.
Highlights: Postoperative flank irradiation is indicated in 20–25% of pediatric renal tumors. For decades, two-opposing beams have been used to cover the flank target volume. Target volumes adjusted for organ shift/motion combined with VMAT were introduced. This new approach resulted in a 2-year loco-regional control rate of 94%. Two locoregional relapses, unavoidable by two-opposing photon beams, were observed. Abstract: Background and purpose: In pediatric renal tumors, conventional two opposing photon beams have been used to cover the postoperative flank target volume for decades. This single center study describes the locoregional outcome using highly conformal flank target volumes adjusted for postoperative changes and intra-fraction motion combined with Volumetric-Modulated Arc Therapy (VMAT). Materials and methods: Between 01-2015 and 12-2019, 36/161 newly diagnosed patients with renal tumors underwent flank only irradiation ( n  = 30) or flank + whole lung irradiation ( n  = 6) using highly conformal target volumes in line with the SIOP-RTSG consensus statement. VMAT consisted of full-arc 10MV photon beams optimized for constraints of the organs at risk. In case of locoregional relapses, image co-registration and dose reconstruction was performed. Each relapse was classified as either 'infield' (V95%relapse : ≥99.0%), ' marginal' (V95%relapse : 20.0–98.9%) or ' outfield' (V95%relapse : 0–19.9%). Results: At a median follow-up from diagnosis of 3.1 years (range:0.4–5.7), the estimated 2-year Locoregional Control Rate, Disease-Free Interval and Overall Survival were 94%, 91% and 94%, respectively. Locoregional relapse was observed in two patients. One patient had a combined tumor bed and regional recurrence, classified as infield (V95%relapse : 100%) and outfield (V95%relapse : 1.2%). The second patient had a regional relapse in the inferior vena cava classified as marginal recurrence (V95%relapse : 93%). Relapses would not have been adequately covered by conventional beams. Conclusions: This single center analysis provides encouraging evidence that excellent locoregional control can be obtained by using highly conformal flank target volumes with VMAT in pediatric renal tumors. The safety of this approach will be validated in a prospective multicenter study.